What Do You See? Healthy Dating That Leads to Healthy Marriage - Victor W. Harris; Ginny Hinton (EDIS)
Albert Einstein offered this perspective on dating and romantic relationships: “Any man who can drive safely while kissing a pretty girl is simply not giving the kiss the attention it deserves.” Dating relationships are the building blocks for healthy marriage relationships. To give them “the attention they deserve,” use different perspectives to help see why healthy dating can lead to healthy marriages or why unhealthy dating can lead to unhealthy marriages and divorce. This 4-page fact sheet was written by Victor W. Harris and Ginny Hinton, and published by the UF Department of Family, Youth and Community Sciences, September 2012.